2021
DOI: 10.1088/1748-605x/abf88c
|View full text |Cite
|
Sign up to set email alerts
|

Carbamoylated chitosan hydrogels with improved viscoelastic properties and stability for potential 3D cell culture applications

Abstract: We demonstrate a benign and straightforward method to modify the chitosan (CH) by carbamoylation. The free amines on CH are converted into carbamyl functionalities by reacting with potassium cyanate (KCNO). One wt% CH solution, when reacted with KCNO ⩾ 0.1 M, leads to the sol–gel transition of CH through the hydrogen bonding to form carbamoylated chitosan (CCH) hydrogel. Gelation time of CCH decreases with an increase in the KCNO concentration and an interconnected porous network is formed as observed under SE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 47 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Cytotoxicity study for α-Syn PFF and chemical inhibitors of endocytosisThe toxicity study of the α-Syn PFF was done on undifferentiated SH-SY5Y cells and differentiated neurons, whereas undifferentiated SH-SY5Y cells were used to study the toxicity of the chemical inhibitors (Pitstop-2, Dynasore, Lactose, MβCD, Wortmannin, Cytochalasin-D and Blebbistatin) of the endocytosis. The alamarBlue assay was used for studying cell toxicity, as explained previously 49. The undifferentiated SH-SY5Y cells were maintained in DMEM/F-12 complete media supplemented with FBS (10%) and Pen-Strep (1%) in a 5% CO 2 incubator at 37 C. When the undifferentiated SH-SY5Y cells' confluence reached 80-90%, the cells were trypsinized with 0.25% trypsin, cell counting was done by hemocytometer, and 2-4 Â 10 5…”
mentioning
confidence: 99%
“…Cytotoxicity study for α-Syn PFF and chemical inhibitors of endocytosisThe toxicity study of the α-Syn PFF was done on undifferentiated SH-SY5Y cells and differentiated neurons, whereas undifferentiated SH-SY5Y cells were used to study the toxicity of the chemical inhibitors (Pitstop-2, Dynasore, Lactose, MβCD, Wortmannin, Cytochalasin-D and Blebbistatin) of the endocytosis. The alamarBlue assay was used for studying cell toxicity, as explained previously 49. The undifferentiated SH-SY5Y cells were maintained in DMEM/F-12 complete media supplemented with FBS (10%) and Pen-Strep (1%) in a 5% CO 2 incubator at 37 C. When the undifferentiated SH-SY5Y cells' confluence reached 80-90%, the cells were trypsinized with 0.25% trypsin, cell counting was done by hemocytometer, and 2-4 Â 10 5…”
mentioning
confidence: 99%
“…Human skin is a viscoelastic material with a storage modulus, G', of approximately 362 Pa and a loss modulus, G'', of 92 Pa. 68 The hydrogels in our optimized construct are on the same order of magnitude, with storage moduli of 270 and 355 Pa and loss moduli of 20 and 36 Pa. Additionally, the viscoelastic properties of the single polymer hydrogels of collagen, fibrin, GelMA, and PEGDA had similar values to those observed in previous studies. [69][70][71][72][73][74][75] When the ECM proteins are with GelMA the storage modulus is decreased compared to GelMA alone, indicating that the inclusion of the ECM proteins results in a softer hydrogel. Comparing the composition of the top and bottom hydrogels of the optimized construct, the bottom hydrogel has 7% GelMA, has a higher concentration of Col1, and includes fibrin which also forms a hydrogel on its own.…”
Section: Discussionmentioning
confidence: 99%
“…Mainardi et al synthesized gels using CH-alginate polyelectrolyte complex with alumina nanoparticles, followed by covalent cross-linking using genipin . Marapureddy et al have reported the preparation of CH-based hydrogels by carbamoylation using potassium cyanate (KCNO), which replaces the free amine in CH with a carbamyl group and induces hydrogen bonding to form a 3D network …”
Section: Introductionmentioning
confidence: 99%
“…21 We have previously shown that carbamoylation of CH improves the viscoelastic properties of the hydrogels, with a G′ between 0.72 Pa and 20 kPa, varying with the KCNO concentration. 9 In the present work, we investigate the effect of adding KCNO along with incorporating GO as a nanofiller and the dependence of CH M w on the physical and rheological properties, and biocompatibility of these hydrogel scaffolds. Specifically, CH with M w of 50 to 90 kDa (LCH) and with 195 to 310 kDa (MCH) have been utilized.…”
Section: Introductionmentioning
confidence: 99%